Poder, biopolítica e governamentalidade em Michel Foucault - Joao Paulo Ayub da Fonseca (2009)
This paper is a study of part of Michel Foucaults work. More precisely, it concerns an investigation of the themes of the power, biopolitics and governamentability, which, in the seventies, figured in Foucaults writings and reflections. The present work investigates these different themes, considering the route throw which the author was taken to deal with them in distinct ways, taking into account that common elements to these, as the power relations and the management of life, are analyzed under different perspectives. One suggests that the changes operated by Foucault between the themes and perspectives of analysis, in no way requiring a theoretical framework that systematize them, enriches his work, which was realized in a continuous exercise of problematization of the issues posed by it.